A NEW TAPEWORM FROM OVIS BHARAL AT JALNA, INDIA - BORDE, S.N.; SHINDE, G.B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1999)
This paper contains the description of a new species of genus Moniezia (Blanchard, 1891). Moniezia jalnaensis n.sp. possess distinguishing characters, such as scolex squarish, slightly broader than long, mature segment squarish, broader than long, testes oval, scattered almost in the middle of the segments, 150-160 in number, cirrus pouch situated in the anterior half of the segments, ovary large, horse-shoe shaped, with numerous short, blunt, round acini; vagina; thin, situated posterior to the cirrus pouch, genital pores oval, bilateral, marginal, situated just anterior to the middle of the segments, vitelline gland on each side, large, postovarian, situated in the concavity of ovarian lobes. The interproglottidal glands oval, situated in the middle region, leaving space on each lateral side 19 in number.